Role and clinical utility of pramipexole extended release in the treatment of early Parkinson's disease - Hametner EM (Dove Medical Press, 2012)
Eva-Maria Hametner, Klaus Seppi, Werner PoeweDepartment of Neurology, Innsbruck Medical University, Innsbruck, AustriaAbstract: The aim of this article is to provide a short review of the most relevant pharmacological and clinical data on pramipexole extended release (ER) as well as to address the clinical utility and potential advantages of a once-daily formulation especially in the treatment of early Parkinson's disease (PD). Pramipexole is widely established as a symptomatic treatment in early as well as advanced PD. The development of an ER formulation, with stable pramipexole plasma concentration over 24 hours, now offers a bioequivalent once-daily alternative. Double-blind randomized controlled trials in early and advanced PD, have established noninferiority of pramipexole ER compared with immediate release as well as superiority of both formulations over placebo. The overnight switch from the standard to the once-daily formulation was shown to be successful in >80% of patients without requiring any dose adjustments. Potential benefits of the prolonged-release design, which have not yet been formally demonstrated in the pivotal trial program, include improved compliance and a potential for better symptomatic control, particularly in patients with early disease that can be managed with monotherapy.Keywords: pramipexole, Parkinson's disease, extended release, compliance, control